Respon Pertumbuhan Dan Produksi Tanaman Kedelai (Glycine max L) Terhadap POC Enceng Gondok - Berliando Kekak; Andi Muhibuddin; Amirudin Amirudin (PALLANGGA: Journal of Agriculture Science and Research, 2026)
This research was carried out at the Integrated Farming System Education Garden, Faculty of Agriculture, Bosowa University, on JL. Raya Poros Sapayya, Bontoramba Village, Palangga District, Gowa Regency, South Sulawesi. This research started from May to July 2024. This research used a Randomized Block Design (RAK) with 5 treatments, namely P0 (without water hyacinth POC as a control), P1 (10 ml water hyacinth POC), P2 (20 ml water hyacinth POC), P3 (30 ml POC water hyacinth) and P4 (40 ml POC water hyacinth) and 3 repetitions. The parameters observed were plant height, stem diameter, number of pods, weight of the pods contained, weight of seeds 100 g/plot, weight of seeds per planting.  The results of the research showed that the best growth and production was in the P4 treatment with a dose of 40 ml which was able to provide growth and production in plant height, stem diameter, number of pods, weight of filled pods, seed weight of 100 g/plot, weight of seeds per planting. Penelitian ini dilaksanakan di Kebun Pendidikan Integrated Farming System Fakultas Pertanian Universitas Bosowa, di JL. Raya Poros Sapayya, Desa Bontoramba, Kecamatan Palangga, Kabupaten Gowa Sulawesi Selatan. Penelitian ini dimulai pada bulan Mei sampai Juli 2024. Penelitian ini menggunakan Rancangan Acak Kelompok (RAK) dengan 5 perlakuan yaitu P0 (tanpa POC enceng gondok sebagai kontrol), P1 (10 ml POC enceng gondok), P2 (20 ml POC enceng gondok), P3 (30 ml POC enceng gondok) dan P4 (40 ml POC enceng gondok) serta 3 ulangan. Parameter yang diamati adalah tinggi tanaman, diameter batang, jumlah polong, berat polong berisi, berat biji 100 g/ plot, berat biji pertanama.  Hasil penelitian menunjukan pertumbuhan dan produksi terbaik yaitu pada perlakuan P4 dengan dosis 40 ml yang mampu memberikan pertumbuhan dan produksi pada tinggi tanaman, diameter batang, jumlah polong, berat polong berisi, berat biji 100 g/ plot, berat biji pertanaman.